Pengaruh Pelatihan SADARI terhadap Perilaku Remaja Anak Jalanan di Komunitas Peduli Anak Jalanan (KOPA) Medan - Sitohang, Nur Asnah; Asiah, Nur; Suza, Dewi Elizadiani (Jurnal Riset Hesti Medan, 2023)
Breast cancer is a malignancy of breast tissue that may arise from the epithelium of the ducts or lobules. Preventive measures by carrying out early detection by self-examination of the breast (BSE) can help find symptoms of breast cancer at an early stage so that the treatment given has high success. Street children are teenagers who are on the streets every day to get a source of life such as food, clothing and other living expenses. These adolescents are also susceptible to breast cancer if they are not given early education about breast cancer prevention. The objectives of this activity are (1) to form youth reproductive health cadres whose function is to educate and train their peers about BSE, (2) increase the knowledge and skills of street children about BSE, (3) early detection of breast cancer in street children (4) there is an immediate solution if there are adolescents who have detected symptoms of breast cancer. The activity was carried out in March 2023 at the Medan Maimun Lurah office. The research design was a quasi-experiment, the sample technique was the total sample, the number of samples was 42 people and the data analysis was the dependent t test. Health education is carried out 3 times a week with a duration of 1 hour. The material presented includes breast cancer (definition, causes, early detection, treatment and complications) and BSE (definition, purpose, benefits, tools and procedures); BSE examination training is carried out 5 times a week for 1 hour. The characteristics of the street children who participated in the activity showed that the majority of the youth were aged 16-20 years (90.47%), high school education (88.09%), Islam (90.47%) and Javanese (59.53%). The results of statistical tests on the effect of BSE training on knowledge obtained a value of P = 0.001 (<0.05) so it can be concluded that there was an effect of BSE training on adolescent knowledge, on attitudes obtained by a value of P = 0.001 (<0.05) so it can be concluded that there was an effect of BSE training on adolescent attitudes, to action obtained P value = 0.001 (< 0.05) so it can be concluded that there is an effect of BSE training on adolescent actions. This activity is proven to be able to increase the knowledge, attitudes and actions of adolescents towards BSE. Therefore it is hoped that the heads of KOPA and PUSKESMAS will carry out routine activities by empowering adolescents who have been trained.